Regulatory Justification of the Fundamental Concepts of Ergonomics in Wheeled Agricultural Machinery - Egorova, Irina; Petrenko, Nadezhda; Tokareva, Anna; Panchenko, Sergey; Kalinin, Aleksandr (International Journal of Integrated Engineering, 2021)
A single-seated man-machine system (MMS) is formed when a person starts controlling a technical device or unit, while undergoing production processes. Production tasks for MMS are developed by the senior system and contain output work parameters, which are determined by the properties of the human operator and the technical subsystem. The purpose of the paper is to demonstrate the process of ensuring the working conditions of a single-seated MMS, the difficulties that arise upon performing tasks, including the content of regulatory acts, which are the technical foundation for the formation of the quality of operation of a single-seated MMS. Study results indicate external and internal restrictions that influence the efficient work of the human operator and are not provided for in regulatory standards, including ways to solve existing restrictions.